2015
DOI: 10.1101/gr.193995.115
|View full text |Cite
|
Sign up to set email alerts
|

Subcellular RNA profiling links splicing and nuclear DICER1 to alternative cleavage and polyadenylation

Abstract: Alternative cleavage and polyadenylation (APA) plays a crucial role in the regulation of gene expression across eukaryotes. Although APA is extensively studied, its regulation within cellular compartments and its physiological impact remains largely enigmatic. Here, we used a rigorous subcellular fractionation approach to compare APA profiles of cytoplasmic and nuclear RNA fractions from human cell lines. This approach allowed us to extract APA isoforms that are subjected to differential regulation and provide… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
83
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 78 publications
(87 citation statements)
references
References 64 publications
(74 reference statements)
4
83
0
Order By: Relevance
“…This was observed initially in a global analysis of all transcribed sequences in human cells 37 , and a more recent study found that ∼10% of all detected 3′ UTR-APA isoforms differed significantly in abundance between nuclear and cytoplasmic fractions 36 . Although nuclear retention was reported for long isoforms containing certain cis elements in the aUTR, such as inverted Alu repeats 38 , it is still uncertain how much of the differential localization of the long isoforms is due to differences in mRNA stability rather than differences in nuclear export.…”
Section: Apa In 3′ Utrsmentioning
confidence: 75%
See 2 more Smart Citations
“…This was observed initially in a global analysis of all transcribed sequences in human cells 37 , and a more recent study found that ∼10% of all detected 3′ UTR-APA isoforms differed significantly in abundance between nuclear and cytoplasmic fractions 36 . Although nuclear retention was reported for long isoforms containing certain cis elements in the aUTR, such as inverted Alu repeats 38 , it is still uncertain how much of the differential localization of the long isoforms is due to differences in mRNA stability rather than differences in nuclear export.…”
Section: Apa In 3′ Utrsmentioning
confidence: 75%
“…Isoforms with a long 3′ UTR tend to be more abundant in the nucleus than in the cytoplasm 36,37 . This was observed initially in a global analysis of all transcribed sequences in human cells 37 , and a more recent study found that ∼10% of all detected 3′ UTR-APA isoforms differed significantly in abundance between nuclear and cytoplasmic fractions 36 .…”
Section: Apa In 3′ Utrsmentioning
confidence: 99%
See 1 more Smart Citation
“…Bottom: number of transcripts in each group. Nuclear/ cytoplasmic transcript level data are from Neve et al (2016).…”
Section: Figurementioning
confidence: 99%
“…34 However, it is still not clear whether premature termination is linked to functional recognition of poly (A) sites. 35 To understand the spatial relationship between poly(A) sites and premature termination caused by kinase inhibition, it will be necessary to accurately map both the point of termination and the co-transcriptional usage of poly(A) sites as represented by nuclear RNA rather than total RNA. The newly-developed base-pair resolution techniques for nascent elongation transcript sequencing (NETseq) and precision nuclear run-on (PRO-Seq) in human cells will help to more accurately map termination.…”
Section: Outstanding Questionsmentioning
confidence: 99%